Physiconomics and a claim for transdisciplinarity in economics - Estrella Trincado (Humanities & Social Sciences Communications)
Abstract In this paper, a claim for transdisciplinary in economics is put forward, pleading for a change of paradigm in economics and the introduction of a new area of study, physiconomics. William Stanley Jevons is presented as a forerunner of this transdisciplinary view. He introduced an emphasis on the importance of the relationship between economics and other social sciences. However, the article is not a historical re-evaluation but an intellectual discussion encouraging the emancipation of economics from engineering in favour of physics, sociology, law and psychology.